2021
DOI: 10.1038/s41598-020-80235-y
|View full text |Cite
|
Sign up to set email alerts
|

Collapsed mitochondrial cristae in goat spermatozoa due to mercury result in lethality and compromised motility along with altered kinematic patterns

Abstract: Earlier we have reported mercury-induced alterations in functional dynamics of buck spermatozoa through free radicals-mediated oxidative stress and spontaneous acrosome reaction. Based on our earlier findings, we aimed to investigate the effect of mercury exposure on motility, kinematic patterns, DNA damage, apoptosis and ultra-structural alterations in goat spermatozoa following in vitro exposure to different concentrations (0.031–1.25 µg/ml) of mercuric chloride for 15 min and 3 h. Following exposure of sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…In goats, a recent study investigated the detrimental effects of the presence of mercury on sperm structure [ 83 ]. Essentially, mercury was found to cause alterations in plasma, acrosome and mitochondrial membranes, as well as alterations in the axoneme.…”
Section: Aquaporins In Mammalian Spermmentioning
confidence: 99%
See 1 more Smart Citation
“…In goats, a recent study investigated the detrimental effects of the presence of mercury on sperm structure [ 83 ]. Essentially, mercury was found to cause alterations in plasma, acrosome and mitochondrial membranes, as well as alterations in the axoneme.…”
Section: Aquaporins In Mammalian Spermmentioning
confidence: 99%
“…Together with the results of a previous work [ 84 ], in which mercury was added to capacitation medium, the effects of this molecule are in agreement with those described in other species. Remarkably, Kushawaha et al [ 83 ] proposed the potential mechanisms leading to the observed consequences in sperm structure and physiology, but AQPs were not contemplated. Considering the sperm damage observed due to the presence of mercury in different species, a potential role of AQPs in the detrimental impact induced by this agent should not be discarded ( Figure 5 ).…”
Section: Aquaporins In Mammalian Spermmentioning
confidence: 99%
“…Furthermore, infertile, and sub-fertile men have higher mercury levels than the fertile men [80] and tubular atrophy and Sertoli-cell-only syndrome has been observed among infertile patients that have been exposed to mercury [81]. Kushawaha et al [39,40] reported that in-vitro exposure of mercuric chloride (0.031 μg/mL) leads to significant increase in spontaneous acrosome reaction, intracellular Ca 2+ and cAMP levels, and capacitation failure may be due to inhibition of 55, 70, and 80 kDa tyrosine phosphorylation of protein. Proteins of 80 and 105 kDa are the main substrates for enzymes and are important in acrosome reactions [82][83][84].…”
Section: Effect Of Mercuric Chloride On Tyrosine Phosphorylationmentioning
confidence: 99%
“…Cyclic-AMP regulation and Ca 2+ influx are the key events of capacitation. In-vitro exposure of goat's spermatozoa to mercuric chloride is reported to increase the intracellular Ca 2+ release and alter the cAMP levels that leads to spontaneous acrosome reaction and inhibition of tyrosine phosphorylation [39,40]. The primary downstream target of cAMP is protein kinase-A (PKA), whose activity increases during sperm capacitation [41].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in sperm motility is also due to the reduction in the mitochondrial membrane potential of spermatozoa following contact with pathogens [ 13 ]. A study by Kushawaha et al revealed that E. coli induces damage to the sperm head and compromises the acrosome, leading to cell death and impaired acrosome reaction [ 14 ]. Other important effects of E. coli on sperm are the increase in intracellular reactive oxygen species (ROS) levels and DNA fragmentation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%